DETERMINANTS OF STUDENTS’ ACADEMIC ACHIEVEMENT IN PUBLIC SECONDARY SCHOOLS IN MACHAKOS COUNTY, KENYA - NJOROGE, ELIZABETH NJOKI (MksU Press, 2023)
Students' academic achievement is one of the indicators of quality education. This study aimed to establish the determinants of students' academic achievements in public secondary schools in Machakos County. Establishing whether students' entry behaviour, the learning environment, the student's teacher ratio, and the teacher's years of experience play an essential role in students' academic achievements. The researcher adopted a descriptive survey research design, and the target population for the study was 369 principals, 4,267 teachers, and 115,132 students. The researcher used purposive and stratified sampling techniques to extract the actual sample size for the study. The sample size was 37 principals, 390 teachers, and 397 students. The researcher used questionnaires to collect data from the teachers, students, and principals. The reliability of the research tools was determined using the test-retest method. Supervisors appraised the validity of the instruments to ascertain and clarify that the test instruments would measure what they were intended to measure. The researcher analyzed Qualitative data by organizing them thematically according to the objectives and labelled the themes for distinction. Quantitative data was analyzed with the help of Statistical Package of Social Sciences (SPSS) Version 28, applying descriptive statistics of mean, mode, standard deviation, frequency tally, and percentages from the research findings. The researcher used inferential statistics of ANOVA and made inferences from the analysis. Results showed that; there is no statistically significant relationship between students' entry-level and academic achievement (p = .863). There is a statistically significant relationship between the learning environment and student’s academic achievement (p = .000). There is no statistically significant relationship between the student-teacher ratio and students' academic achievement (p = .597). There is a statistically significant relationship between teacher experience and students' performance (p = .000). The study recommends that; the principals collaborate with other stakeholders to ensure a conducive learning environment for effective learning. Moreover, the government should provide the necessary learning resources and ensure that secondary schools' infrastructure is well-equipped. In conjunction with TSC, the ministry of education should improve the frequency of organizing workshops/seminars and in-service training for teachers.